Penerapan Metode Vertikal Pada Sistem Informasi Akuntansi Keuangan Dalam Divisi Keuangan Puskesmas Patebon - Yuni Handayani; Rahmi Darnis (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2023)
Increasingly sophisticated technological developments require an information system that produces valid information including this study discussing the Patebon Public Health Center reporting system including recording income, recording costs, and presenting financial reports, for this reason as an institution that is developing Public Health Center Patebon requires the development of information technology to achieve better quality. The head of the finance sector, who so far still uses the manual writing format, some of the problems that still often arise are in the preparation of financial reports or profit/loss caused by human error because the recording is also sometimes done soberly. In addition, there is no financial accounting information system that meets the financial department so it often experiences several problems related to financial data management. The method that the author uses in the Financial Information System uses the vertical method. Vertical analysis is an analysis performed on only one period of financial statements. The analysis is carried out between existing posts, in one period. The information obtained is only for one period and no progress is known from period to period